From Classic Labor to the Labor of the "General Intellect": The Impact of the Digital Intelligence Era on Socialist Labor Theory. - LI, TE (Monthly Review: An Independent Socialist Magazine, 2026)
The article focuses on Marxist labor theory as the foundation of historical materialism and surplus value analysis in understanding how capitalist production operates and develops. Topics include the essential nature of labor as a human–nature "metabolism," the dual character of labor in Marxist theory, and the production of surplus value within capitalist economic systems.